Effects of genistein on lipopolysaccharide-induced injury of mouse alveolar epithelial cells and its mechanism. Issue 3 (3rd March 2020) - Zhu, Qi; Zhang, Wei; Mu, Deguang; Zhou, Hongbin; Wu, Shengchang; Zou, Hai
ABSTRACT: Alveolar and bronchial epithelial cells have critical functions in acute respiratory distress syndrome progress. Genistein could protect the lungs from acute lung injury, however, whether genistein protects the alveolar epithelial cells from LPS-induced injury was less studied. Spectrophotometric method 3-[4, 5-dimethylthiazol-2-yl]-2, 5-diphenyltetrazolium bromide (MTT) and enzyme-linked immunosorbent assay (ELISA) were performed to detect cell viability and levels of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and IL-6. Flow cytometry and western blot assay were performed to detect cells apoptosis and protein levels. In LPS-induced model of mouse lung epithelial (MLE)-12 cells, PBEF (proinflammatory cytokine) expression, and cell apoptosis were increased and cell viability was decreased, whereas NF-κB was activated and expression levels of TNF-α, IL-1β, and IL-6 were increased. However, genistein partly reversed the effect of LPS, and it plays a protective role in lung injury by reducing expression of PBEF, inhibiting the activation of NF-κB and alleviating inflammatory response of cells. Graphical abstract: : LPS increased the alveolar epithelial cell injury, and GEN suppressed the activation of NF-κB by reducing the of PBEF expression, reducing the inflammatory response of cell.